Film Animasi sebagai Media Pembelajaran Kekritisan Penalaran Anak Usia Sekolah Dasar pada Masyarakat Multibudaya di Indonesia - Pratiwi, Yuni (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
This study aims at developing animated movie series for children as learning media to boost Indonesian young learners’ critical thinking. The product specification is as follows: (1) animated movie series help children practice their critical thinking using the designed patterns; (2) the content of the movie contains moral values for character building in Indonesian multicultural society; (3) the language exposure in the animated series is comprehensible for children; and (4) the development of the story is through naturalistic style. The design of this study is adapted from R2D2 (Recursive, Reflective, Design and Development) by Willis (1995). The result of this study is six animated movies which has been tried out for the designed participants.